1992
DOI: 10.1088/0957-0233/3/8/002
|View full text |Cite
|
Sign up to set email alerts
|

Densimeter calibration method versus temperature and pressure

Abstract: This article reports a calibration procedure for the commercial Anton Paar DMA 512 densimeter usable at pressures up to 40 MPa. The method is based on water as a reference substance and requires knowledge of the characteristics of the cell as functions of temperature when subjected to a vacuum lower than 100 Pa. Comparis on with data from the literature indicates a relative accuracy of 0.1% where the classical calibration method (i.e. assuming no dependence of the densimeter performance upon pressure) led to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
184
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 234 publications
(197 citation statements)
references
References 11 publications
7
184
2
Order By: Relevance
“…The estimated uncertainty of the measured temperature is ±0.01 K between (293.15 and 353.15 K) (Anton Paar MKT50 thermometer) while the estimated uncertainty of the measured pressure is ±0.015 MPa (Presents Precise Gold Plus pressure transmitter); as a consequence, the uncertainty on the density measurement is estimated to be ±0.5 kg m −3 (i.e., around 0.05% for density close to that of water). This uncertainty is similar to that reported in several other studies [14][15][16][17].…”
Section: High-pressure Density Measurementsupporting
confidence: 91%
“…The estimated uncertainty of the measured temperature is ±0.01 K between (293.15 and 353.15 K) (Anton Paar MKT50 thermometer) while the estimated uncertainty of the measured pressure is ±0.015 MPa (Presents Precise Gold Plus pressure transmitter); as a consequence, the uncertainty on the density measurement is estimated to be ±0.5 kg m −3 (i.e., around 0.05% for density close to that of water). This uncertainty is similar to that reported in several other studies [14][15][16][17].…”
Section: High-pressure Density Measurementsupporting
confidence: 91%
“…The spring constant was assumed to be independent of pressure and its temperature dependence was represented by a fourth-order polynomial, while the tube volume was assumed to vary linearly with pressure and as a cubic function of temperature. The assumptions made regarding pressure dependence of the parameters were consistent with the second method described by Lagourette et al 8 and Sousa et al 9 although many more parameters were used to describe empirically the temperature variation of the apparatus parameters given the much wider range of operating temperature.…”
Section: Ideally the Calibration Measurements Used To Determine A(pmentioning
confidence: 92%
“…None of these, however, have been tested over the wide range of conditions considered in this work, namely pressures to 140 MPa and temperatures from 273 to 473 K. In 1992 Lagourette et al 8 and Sousa et al 9 independently described methods for calibrating VTDs supplied by Anton Paar, including the model DMA 512 which is a stainless steel VTD operable at pressures to 40 MPa and temperatures to 423 K. These calibration methods involved the determination of the evacuated tube's resonance period as a function of temperature and the use of an assumption regarding the pressure dependence of A or B, which was informed by a physical model of the vibrating tube. In one method 8 , only B was assumed to vary (linearly) with pressure whereas in the second method 8,9 A and B were assumed to have the same pressure coefficient so that the ratio A/B was independent of pressure. Lagourette et al 8 found the first method resulted in a calibration that represented the reference fluid densities slightly better, although the second method has a more physical basis (as will be seen below).…”
Section: Ideally the Calibration Measurements Used To Determine A(pmentioning
confidence: 99%
See 1 more Smart Citation
“…For a vibrating tube density sensor (Lagourette et al, 1992), the relationship between the density and the resonance frequency is…”
mentioning
confidence: 99%